Studying the Bound State of the BK¯ System in the Bethe-Salpeter Formalism - Zhen-Yang Wang; Jing-Juan Qi; Xin-Heng Guo (Advances in High Energy Physics)
In this work, we study the BK¯ molecule in the Bethe-Salpeter (BS) equation approach. With the kernel containing one-particle-exchange diagrams and introducing two different form factors (monopole form factor and dipole form factor) in the vertex, we solve the BS equation numerically in the covariant instantaneous approximation. We investigate the isoscalar and isovector BK¯ systems, and we find that X5568 cannot be a BK¯ molecule.